STUDENT ADMINISTRATIVE SYSTEM OF PAYMENT IN USING MICROSOFT SMK XXX VISUAL BASIC 6 - Irvan Nurdian; Yuce Yuliani, SKom, MMSI Yuce Yuliani, SKom, MMSI (Jurnal Sistem Informasi, 2005)
Tuition payment system has a lot of data and any time required, and obviously thiswill take quite a long time if done manually, also frequently encountered problems orweaknesses that exist, which are not orderly recording data , has not been sorted orcomposed neatly and when payment has not done a good procedure, so that any timethe data required will require a long time in the query.Because the above problem, I am interested to try out ideas so that problems can besolved quickly and accurately. At this writing the author using Visual Basic softwarebecause it has facilities that support in making applications programs, with the writertrying to create a computer program on the CMS Administration System Design onSMK XXX.